MATH SOLVE

5 months ago

Q:
# Mario simplified the expression as shown. Which statement explains Mario’s error?

Accepted Solution

A:

Answer: Last optionStep-by-step explanation: 1. According to the properties of exponents, you have that:[tex]a^{-n}=\frac{1}{a^n}\\\\(a^n)^m=a^{mn}[/tex] 2. Then, he must simplify the expression as following: [tex](4z^8)^{-3}={4^{-3}z^{8(-3)}=\frac{1}{64z^{24}}[/tex] 3. Therefore, as you can see, should have also applied the negative exponent to 4 to get [tex](4z^8)^{-3}={4^{-3}z^{8(-3)}=\frac{1}{64z^{24}}[/tex]